The knowledge, attitudes and practices of the UPCD senior clinicians towards smoking and the cessation of smoking of UPCD patients, SY 2001-2002 - Cambri, Charissa T.; Dela Cruz, Shanylle C.; Sembrano, Marilou (Adviser).
Dental students have learned the ill-effects of smoking in their basic dental education. However, the involvement of dental students in smoking cessation practices as early as in their clinical training is not widely investigated in the Philippines. It is therefore the aim of this study to determine the knowledge, attitudes and practices of the UPCD senior clinicians (school year 2001-2002) towards smoking and the cessation of smoking of UPCD patients and know their relationships. The participants of this study were 72 fourth year dental students. Data was collected using survey questionnaire and was assessed using descriptive statistics. The survey also assessed demographics, like age and gender, and personal tobacco use history. Generally, the population exhibited a high level of knowledge towards smoking and its effects on oral health. A favorable attitude towards cessation of smoking of patients can be seen. But the practice towards helping patients to quit smoking is limited. Very few follow up patients regarding their habit. Of all the characteristics used to describe the respondents, the age and personal tobacco use have a significant relationship towards clinicians' attitudes. Finally, attitudes and practices also have a significant relationship with each other.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Smoking; Smoking cessation; Students, Dental